دور القانون الجنائي الدولي في إنفاذ القانون الدولي الإنساني - عبد الله أحمد كيلان (Journal of Legal Sciences, 2017)
The development of the phenomenon of crime in terms of quantitative and qualitative led to turn this phenomenon from the individual level to the international level... and now a wide range of individual called (victim), maybe thousands and sometimes millions... And from the use of simple primitive methods of killing the lethal weapons... This is the beginning of the international crimes against the security and safety of humanity such as genocide and war crimes and crimes against humanity. Although it is hard to eliminate the crime, the efforts of the international community will necessarily be diverted to prevent the commission of serious crimes and violations or to limit their effects. Since the existence of a judicial organ to deal with disputes of an international character is an effective mean to enforce and comply with the international legal rules governing combat, and there is authority to carry out the task of repudiation and punishment in cases of getting outside the law. To that end, the international community sought to establish the rules of international criminal law and to develop the institutional aspect of international criminal justice through the establishment of bodies to establish criminal conduct and to prosecute those responsible for violating the rules of protection. The term international humanitarian law refers to "the International Set of Rules that deals with the Victims of War and Armed Conflicts, which was codified at the beginning of the twentieth century in The Hague in 1907 and the four Geneva Conventions for the Protection of Victims of Disputes in 1949 and the Additional Protocols thereto, (1977). The international community has recognized the need to apply the principle of criminal accountability for serious violations of the rules of international humanitarian law in the context of providing a repressive mechanism in the event of violations of those legal norms which guarantee the protection of a large part of humanity. In order to improve the mechanisms of protection, they must be exercised at both national and international levels. Therefore, we devoted the first chapter of this study to the role of the national criminal judiciary in the implementation of the rules of international humanitarian law. The second chapter deals with the principle of universal jurisdiction and its role in international justice. The last chapter will be about the status of International Criminal Court and its role in enforcing the rules of international humanitarian law.